If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 33 Reorder the terms: 9 + 3x = 33 Solving 9 + 3x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 33 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 33 + -9 3x = 33 + -9 Combine like terms: 33 + -9 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| 3x^3-18x^2-2x+12=0 | | x^2+49y^2=49 | | X^2+29=0 | | 8x=12x-20 | | 7(v+4)=-4(2v-9)+9v | | 2x=18+2y | | 1250-113= | | x^2+36=7 | | (3x^3-18x^2)(-2x+12)=0 | | 2x-2=3x*6 | | X-2y=11 | | 3(v-1)=3v+3-2(-7v-5) | | -20+8b=3b | | 9x+15+6x+15= | | 2a=6a+12 | | 189=-1k+10 | | 25x^2+4=15 | | -3(4y-3)+4y=3+3(2y-4) | | 3+11x=80 | | n-10= | | 4-3x=23 | | x-12=5x+28 | | 6x-5y=23 | | 6x-57=23 | | n+21= | | -3+9b=36 | | 11j-88=13.2 | | v^2+25v-3750=0 | | 5(x-5)-9=-6(-3x+5)-7x | | 5x^2+4=24 | | 5x^2-2x-4=0 | | 7xn= |